(untitled) (Journal of Organizational Psychology, 2021)
Studies investigating the impact of creativity training on the actual belief in these capabilities have shown contradictory findings and fall short on explaining the underlying mechanisms how people gain or lose confidence in their creative abilities. Following a mixed-methods approach, this study explores how problem-solving style influences the impact of creativity training on creative self-efficacy based on a creativity course at a German university. Style preferences were associated with different experiences of creative mastery and other sources of creative self-efficacy. We discuss the implications of these findings for the design of creativity training courses and developing creative talent in organizations.